Foundations and principles of clinical, institutional and social Bioethics - León Correa, Francisco Javier (Acta Bioethica, 2009)
This article attempts to base the necessity of widening the field of bioethics in Latin America from clinical ethics to a social bioethics, in order to deal with ethical dilemmas in institutions, public health, healthcare policies and reforms, and legislation. The proposal is, on one hand, to incorporate those aspects of its institutional and social dimensions in the academic debate in bioethics. On the other hand, to develop a system of the bioethics of principles, starting from personalism and dialogical ethics of the complementary precepts that may be utilized in the resolution of cases and in the decision-making process.